Analysis of Service Quality of Mitra Mart Online Vegetable Store Using E-Servqual & Importance Performance Analysis (IPA) Method - Fahroby Adnan; Katarina Leba; Beny Prasetyo (Publikasi Indonesia, 2024)
The implementation of online learning necessitates the provision of adequate IT infrastructure support and the dissemination of awareness among all relevant parties, including lecturers, students, and parents. The prevailing pandemic situation has underscored the necessity for such measures encourages the adoption of online learning. Learning Management System (LMS), often referred to as e-learning, plays an important role in facilitating this transition. Another critical aspect to consider is user readiness and acceptance. The Technology Readiness and Acceptance Model (TRAM) is a method that can be used to analyze these factors. This study utilizes TRAM to evaluate the readiness and acceptance of LMS, focusing specifically on lecturer users in the East Java Province area, encompassing both public and private universities. The purpose of this article is to assess the level of readiness and acceptance of LMS among lecturers in East Java and to identify factors influencing their adoption. The findings reveal that the level of readiness among lecturers in adopting LMS tends to be low. Furthermore, several hypotheses related to the use of LMS by lecturers are explored, providing insights into the factors influencing technology adoption in higher education.